A life course approach to understanding stress exposures and cognitive function among middle-aged and older adults. (December 2022) - Chen, Ruijia; Williams, David R.; Nishimi, Kristen; Slopen, Natalie; Kubzansky, Laura D.; Weuve, Jennifer
Abstract: Background: Many studies have evaluated the stress-cognition association, but few have captured the cumulative nature of stress or distinguished the influences of stressors occurring in childhood versus adulthood. Using a lifecourse approach, we investigated whether cumulative stress exposures are associated with poorer cognitive function and faster cognitive decline. Methods: We used data from the Midlife Development in the United States Study ( N  = 3, 954, mean baseline age: 56 years). We fit marginal structural generalized estimating equations models to estimate the difference in baseline cognitive function per SD increment in the continuous stressor score, and, separately, between persons in each life course stressor profile and those who did not experience high stress in either childhood or adulthood. We also characterized differences in cognitive decline across levels of stress exposures. Results: Higher cumulative stress exposure was associated with lower executive function ( difference per SD in continuous stressor score = −0.12 SD units, 95% CI = −0.16, −0.08) and episodic memory ( difference  = −0.09 SD units, 95% CI = −0.13, −0.05). Baseline executive function and episodic memory were lower among those with high stress only in childhood, only in adulthood, and both, than among those without high stress in childhood or adulthood. There was little evidence that rate of change in executive function and episodic memory differed across levels of cumulative stress exposures. Conclusions: These findings offer support to the hypothesis that stress exposures, accumulated over the life course, worsen cognitive performance, but limited support for the hypothesis that these exposures promote cognitive decline. Highlights: More exposure to stressors over the life course was associated with worse cognition. Childhood stress, even absent adult stress, was associated with worse cognition. Higher cumulative exposure to stressors was not associated with cognitive decline.